MOLECULAR IDENTIFICATION OF NEW LOCAL STRAINS OF BIFIDOBACTERIA AND LACTOBACILLI USING 16S RRNA - Sharipova Z.O.,; Yodgorova N.T., (Central Asian Journal of Medicine, 2025)
In light of the growing interest in using probiotic microorganisms in medicine and the food industry, there is an increasing need to develop effective methods for their identification and characterization. This study presents the results of molecular genetic analysis of newly isolated local strains of bacteria from the genera Bifidobacterium and Lactobacillus, obtained from samples collected in Uzbekistan. For identification purposes, methods of amplification and sequencing of the 16S rRNA gene were used, along with species-specific primers when necessary. The obtained nucleotide sequences were compared with NCBI databases, allowing for precise determination of the taxonomic position of the studied isolates. The research revealed the presence of both widely distributed and unique strains with potential for further application in the development of probiotic preparations. The acquired data contribute to expanding knowledge about the biodiversity of probiotic microflora and highlight the significance of local microbiological resources.